Cytokine disturbances in systemic lupus erythematosus - Jacob, Noam (BioMed Central, 2011)
The pathogenesis of systemic lupus erythematosus (SLE) is complex, and the resulting disease manifestations are heterogeneous. Cytokine dysregulation is pervasive, and their protein and gene expression profiles may serve as markers of disease activity and severity. Importantly, biologic agents that target specific cytokines may represent novel therapies for SLE. Four cytokines (IL-6, TNFα, IFNα, and BLyS) are being evaluated as therapeutic targets in SLE. The present review will examine the roles of each of these cytokines in murine and human SLE, and will summarize results from clinical trials of agents that target these cytokines.